2012
DOI: 10.1105/tpc.112.098749
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MYC2 Interacts with DELLA Proteins in Regulating Sesquiterpene Synthase Gene Expression

Abstract: Arabidopsis thaliana flowers emit volatile terpenes, which may function in plant-insect interactions. Here, we report that Arabidopsis MYC2, a basic helix-loop-helix transcription factor, directly binds to promoters of the sesquiterpene synthase genes TPS21 and TPS11 and activates their expression. Expression of TPS21 and TPS11 can be induced by the phytohormones gibberellin (GA) and jasmonate (JA), and both inductions require MYC2. The induction of TPS21 and TPS11 results in increased emission of sesquiterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
393
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(410 citation statements)
references
References 74 publications
14
393
0
3
Order By: Relevance
“…This other class of plantspecific hormones plays crucial roles in the mechanisms promoting plant growth and development, notably by triggering the degradation of plant growth repressors, the DELLA proteins (for review, see Harberd et al, 2009). Reinforcing the role of DELLAs as integrators of plant hormone and environmental change responses, recent studies have shown the interaction of DELLAs with JAZ proteins (Hou et al, 2010;Wild et al, 2012;Yang et al, 2012) as well as the MYC2 transcription factor (Hong et al, 2012;Wild et al, 2012). In addition, DELLAs negatively affect plant organ growth by reducing both cell proliferation and cell expansion (Achard et al, 2009).…”
Section: Meja Reduces Both Cell Division and Cell Expansion And Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…This other class of plantspecific hormones plays crucial roles in the mechanisms promoting plant growth and development, notably by triggering the degradation of plant growth repressors, the DELLA proteins (for review, see Harberd et al, 2009). Reinforcing the role of DELLAs as integrators of plant hormone and environmental change responses, recent studies have shown the interaction of DELLAs with JAZ proteins (Hou et al, 2010;Wild et al, 2012;Yang et al, 2012) as well as the MYC2 transcription factor (Hong et al, 2012;Wild et al, 2012). In addition, DELLAs negatively affect plant organ growth by reducing both cell proliferation and cell expansion (Achard et al, 2009).…”
Section: Meja Reduces Both Cell Division and Cell Expansion And Delaymentioning
confidence: 99%
“…Therefore, more than an exit from proliferation, we observe inhibition and entry in stand-by mode; as a result, both the rate of division and entry into endoreduplication are negatively affected. Interestingly, several analyses report cross talk between JAs and GAs (Navarro et al, 2008;Cheng et al, 2009;Hong et al, 2012;Yang et al, 2012). This other class of plantspecific hormones plays crucial roles in the mechanisms promoting plant growth and development, notably by triggering the degradation of plant growth repressors, the DELLA proteins (for review, see Harberd et al, 2009).…”
Section: Meja Reduces Both Cell Division and Cell Expansion And Delaymentioning
confidence: 99%
“…1). 9,10 The accumulation of carotenoids is also closely linked to the intracellular levels of GA and ABA. Biosynthesis of carotenoids and GA share a common biosynthetic precursor, i.e.…”
Section: Transcriptional Regulation Of Carotenoids Accumulationmentioning
confidence: 99%
“…Similarly, the MYB4 transcriptional factor was a repressor of one of the enzymes in the cinnamate-4-hydroxylase, phenylpropanoid pathway and controlled the flux in petunia flowers (Colquhoun et al 2011). Similarly, MYC2 activated two sesquiterpene synthase genes (TPS11, TPS21) through the jasmonic acid (JA) and gibberellic acid signaling pathway in A. thaliana during inflorescence (Hong et al 2012). In roses, the up-regulation of terpenoid pathways occurred via the overexpression of the PRODUCTION OF ANTHOCYANIN PIGMENT1 (PAP1) transcriptional factor (Zvi et al 2012).…”
Section: Transcriptional and Post-transcriptional Regulationmentioning
confidence: 99%